LEARNING ANXIETY OF CHINESE MAJORED STUDENTS - Vu, Luu Hon (VNU Journal of Foreign Studies; Vol 35 No 5, 2019)
The research surveyed the anxiety levels and the influencing factors during Chinese acquisition of Chinese majored students at several universities in Vietnam. Based on the theory of anxiety in foreign language learning by Horwitz (1986) and Young (1991), we conducted a questionnaire survey with 124 students. The questionnaire results indicate that test anxiety along with listening and speaking anxiety take the top spot in the students’ anxiety levels, whilst, classroom anxiety ranked last. In addition, female students have higher anxiety levels than the opposite sex. Students with shorter Chinese learning time have higher anxiety degrees than the ones with longer learning time. The results also report that age is not an influential factor in terms of the student’s anxiety levels. Students with higher degrees of anxiety end up with lower final results. The core problem that leads to anxiety among Chinese majored students is the features of Chinese.